Imprint of Southern Ocean mesoscale eddies on chlorophyll - Frenger, Ivy; Münnich, Matthias; id_orcid:0 000-0003-3292-2934; Gruber, Nicolas; id_orcid:0 000-0002-2085-2310 (Copernicus, 2018)
Although mesoscale ocean eddies are ubiquitous in the Southern Ocean, their average regional and seasonal association with phytoplankton has not been quantified systematically yet. To this end, we identify over 100000 mesoscale eddies with diameters of 50km and more in the Southern Ocean and determine the associated phytoplankton biomass anomalies using satellite-based chlorophyll-a (Chl) as a proxy. The mean Chl anomalies, δChl, associated with these eddies, comprising the upper echelon of the oceanic mesoscale, exceed ±10% over wide regions. The structure of these anomalies is largely zonal, with cyclonic, thermocline lifted, eddies having positive anomalies in the subtropical waters north of the Antarctic Circumpolar Current (ACC) and negative anomalies along its main flow path. The pattern is similar, but reversed for anticyclonic, thermocline deepened eddies. The seasonality of δChl is weak in subtropical waters, but pronounced along the ACC, featuring a seasonal sign switch. The spatial structure and seasonality of the mesoscale δChl can be explained largely by lateral advection, especially local eddy-stirring. A prominent exception is the ACC region in winter, where δChl is consistent with a modulation of phytoplankton light exposure caused by an eddy-induced modification of the mixed layer depth. The clear impact of mesoscale eddies on phytoplankton may implicate a downstream effect on Southern Ocean biogeochemical properties, such as mode water nutrient contents. ISSN:1726-4170 ISSN:1726-4170